Effect of soil models on the prediction of ground settlement due to tunnelling - Chua, Chin Hiang. (2008)
This project discusses primarily prediction of ground settlement due to tunnelling using the different constitutive soil models offered in PLAXIS, a finite element geotechnical analysis program. As a secondary method of analysis, empirical estimation using the inverted normal distribution curve formula is included for comparison.